Persona, natura umana e bioetica attuale (Prima parte): Distinzione e connessione tra natura umana e persona umana - Lucas Lucas, Ramón (Studia Bioethica, 2019)
Of particular importance for bioethics is the contemporary discussion over the distinction and connection between «human nature» and «human person», especially since there are a number of positions which contest the attribution of personhood to each and every human being. This raises serious anthropological, ethical, and juridical questions. While it is correct to distinguish between human nature and human person, this does not necessarily mean that the two exist apart from one another. It is difficult to avoid treating them as separately existing realities, however, if person is identified with the actual possession of a certain set of properties and operations. In this case, the ethical duty to respect persons would only extend to those who exhibit the relevant properties and operation. This paper (in two parts) argues that what makes one a human person, and worthy of respect, is the possession of human nature rather than the actuation of certain properties